Evaluation of early generation progenies, (F2) of fenugreek (Trigonella foenum-graecum L.) crosses for seed yield and yield related characters - Singh, R S Raje, D L Singhania, D (Journal of Spices and Aromatic Crops, 2003)
F2 generation of five crosses of fenugreek were evaluated for seed yield and its components along with parents. F2 generation had wider range than the parents for most of the characters in the crosses. Genetic parameter of variation also indicated that substantial amount of variability was generated in F2 of all the crosses which will be very useful in fenugreek improvement. Pods per plant had high PCV, GCV, heritability and genetic advance as percentage of mean in all the five crosses. Association analysis indicated that pods per plant had positive association with seed yield plant in all the five crosses. On the basis of the present study, selection for pods per plant in F2 generation of fenugreek crosses will be useful for improvement in seed yield.